The Role of Ethnic Culture in Formation of Ideological Immunity in the Youth (Zien Journal of Social Sciences and Humanities, 2023)
The article examines the internal, immanent features of Uzbek ethnoculture, aspects related to the national idea. The national ideological and ideological essence of artistic and aesthetic images and images in Uzbek ethnoculture is revealed. Forming an aesthetic ideal is the main function of Uzbek ethnoculture. In the article, the features of this function, issues of wider use of ethnocultural possibilities for its formation are studied from the point of view of national idea and ideology